Analisis Semiotika Roland Barthes pada Representasi Konflik Batin Akaza dalam Anime Demon Slayer: Infinity Castle - Syifa Urrahmah; Nurhayati Nurhayati; Irhazt Angga Denilza; Muhammad Suhemi (MUKASI: Jurnal Ilmu Komunikasi, 2026)
This study aims to answer how intrapersonal communication within Akaza’s psychological conflict is represented through Roland Barthes’ semiotic analysis in Demon Slayer: Infinity Castle Arc. This research employs a descriptive qualitative method with semiotic analysis consisting of three levels of meaning: denotation, connotation, and myth. The primary data were collected from selected scenes that depict Akaza’s inner struggle through visual expressions, reflective dialogue, and the emergence of past figures that influence his emotional state. The findings indicate that Akaza’s intrapersonal communication is portrayed through flashbacks, self-dialogue, and shifting emotional expressions that reveal tension between his human values and his identity as a demon. At the denotative level, scenes display clear emotional and behavioral changes. At the connotative level, these signs reflect processes of rejection, doubt, and remorse experienced by Akaza. At the myth level, the anime conveys broader social values related to the meaning of strength, moral awareness, and the courage to acknowledge personal mistakes. This study contributes to communication studies by demonstrating how intrapersonal communication can be understood through visual and narrative signs within animated media.